Antiviral Activity of Cytarabine in Herpesvirus–Infected Rats - Renis, Harold E. (1973)
Intranasal inoculation of herpesvirus (approximately 1.8 mean lethal doses [LD(50)] in 0.1 ml) into 105- to 115-g rats produces paralytic disease in 4 to 5 days and 80 to 100% mortality in 8 to 12 days. Cytarabine (ara-C) (40 to 320 mg/kg), administered subcutaneously to inoculated rats, delays the onset of paralysis and protects the animals from death. Drug treatments were given twice daily for 5 days. Beneficial drug effects were observed even when initiation of therapy was delayed for 3 days after virus inoculation. A dose-response relationship existed when therapy was initiated at 4 h after virus inoculation. However, when therapy was delayed for 3 days, it appeared that the highest drug level (320 mg/kg twice daily) was somewhat less effective than the lower doses (160 and 80 mg/kg twice daily). Virus could be detected in homogenates of brain beginning 3 days after inoculation, and the titer increased through 7 days. Ara-C treatment, initiated 4 h after inoculation, caused a delay in the appearance of virus, and a reduction in the titer in the brain homogenates. No virus was detected in blood serum, or in homogenates prepared from lung, kidney, thymus, or spleen of infected rats. The virus titration studies are in agreement with the illness and mortality produced by herpesvirus infection.